Homogenization‐based topology optimization for high‐resolution manufacturable microstructures - Groen, Jeroen P.; Sigmund, Ole (International journal for numerical methods in engineering, 2018)
Summary This paper presents a projection method to obtain high‐resolution, manufacturable structures from efficient and coarse‐scale homogenization‐based topology optimization results. The presented approach bridges coarse and fine scale, such that the complex periodic microstructures can be represented by a smooth and continuous lattice on the fine mesh. A heuristic methodology allows control of the projected topology, such that a minimum length scale on both solid and void features is ensured in the final result. Numerical examples show excellent behavior of the method, where performances of the projected designs are almost equal to the homogenization‐based solutions. A significant reduction in computational cost is observed compared to conventional topology optimization approaches.